Perceived Barriers among Indonesian General Dentists in Providing Caries Preventive Care for Pediatric Patients - Khairinisa, Safira; Setiawati, Febriana; Darwita, Risqa Rina; Maharani, Diah Ayu (European Journal of Dentistry, 2023)
Objective This study aimed to investigate Indonesian dentists' perceived barriers in providing caries prevention for pediatric patients.Materials and Methods A total of 362 general dentists were included in this cross-sectional study. The participants were asked to complete a self-administered online questionnaire of dentist characteristics and perceived barriers in multiple domains (children, parents, dentists, and healthcare system-related barriers). The frequency of responses to items of the questionnaire was presented. The Mann–Whitney U test was used to compare perceived barriers by gender, Kruskal–Wallis by practice sector, and Spearman analysis was used to assess the correlation between perceived barrier with age, years of practice experience, weekly practice hours, percentage of pediatric patients, percentage of pediatric preventive care, and percentage of insured patients. A multivariate analysis was conducted through structural equation modeling.Results The highest perceived barrier was found to be healthcare system-related, followed by parents, children, and dentists themselves. Most participants thought parents have poor knowledge of pediatric caries prevention (n = 290; 80%), and dental care for young children emphasizes curative treatment over prevention (n = 257; 70%). The multivariate analysis showed that dentists' practice sector and age affect perceived barriers and pediatric preventive care the most.Conclusion Factors and barriers identified in this study must be the main focus of oral health programs, and dentists, as service providers, need proper training to address these barriers to optimize caries prevention in Indonesia.
Keywords: preventive dental care; treatment barrier; dentist; Indonesia